Pengembangan Media Monopoli Edukatif Materi Keberagaman Budaya Dengan Penguatan Karakter Cinta Tanah Air di Sekolah Dasar - Agnes Andhika Putra Pratama; M. Zainuddin; Sutansi Sutansi (Sekolah Dasar: Kajian Teori dan Praktik Pendidikan, 2021)
Learning media play an essential role for students to understand learning material. This study aimed to produce educational monopoly media on material cultural diversity by strengthening patriotism in grade IV Elementary School. This development uses the Dick and Carey model. The result of validation by a material expert, media expert, and user get a case of 100 percent, 83.3 percent, and 91.6 percent. Students question results on small-scale tests, and field tests get 93.3% and 92 percent. Educative monopoly can foster a character who loves the motherland with a percentage value of 90 percent.